Asymmetry of muscle strength in elite athletes - Drid, P.; Drapsin, M.; Trivic, T.; Lukac, D.; Obadov, S.; Milosevic, Z. (Biomedical Human Kinetics, 2009)
Study aim: To determine muscle strength variables in elite judoists and wrestlers since thigh muscle strength and bilaterally balanced flexor-to-extensor ratio minimise injury risk and are desirable for achieving sport successes.